Define and design a mathematical model moderating role of psychological empowerment on the role of education in improving the quality of professors - سعید مرادی; بتول فقیه آرام; نادر برزگر; پری سوسهابی (Allameh Tabataba'i University Press, 2015)
The aim of this study was to define and design a mathematical model moderating role of psychological empowerment on the role of education in improving the quality of professors was. The aim of this research is applied and the method of data collection is descriptive and correlation. The population of the study area 1019 of eight faculty members of Tehran Islamic Azad University in the academic year 1394-1395 has been engaged in teaching and research. A sample of 279 people using Cochran formula and stratified random sampling method was used. All questionnaires performance of departments, completed the performance and empowerment. The validity of these questionnaires through face validity was approved by the faculty. As well as to help Cronbach's alpha coefficient of reliability of average educational groups operate 0.76, 0.81 and empowerment faculty members' performance was 0.82. The questionnaires were distributed data using Pearson correlation test, confirmatory factor analysis, path analysis and 8.5 Lisrel 21 SPSS statistical software were analyzed. The results showed that the role of the departments has significant impact on the quality of performance and psychological empowerment of university professors.